SWIMMING CLASSES FOR BABIES: THE MOTOR STIMULATION IN LIQUID ENVIRONMENT, FOR SOME BABIES, BETWEEN ZERO MONTHS AND SIX MONTHS OF AGE, WHO SHOWS DIFICULTIES IN RECUPERATING THE NATURAL PROCESS OF MOTOR DEVELOPMENT, CAUSED BY THE LOST OF EPIGLOTTIS'S REFLE (Fiep Bulletin - online, 2015)
The neonate baby is adapting in extra uterine life and he has been born with or has developed a repertoire of reflexes that allows him to live in this new cosmos on his first's months of life. The motor development is the human development basis. It is through the body that Human Being is capable of discover the world that surround him. The reflexes form the first stage of motor development, which can become voluntary movements or be lost according to its use. About baby's reflexes, since his birth to six months years old, it is found the Epiglottis Reflex. This kind of reflex allows babies to extend and flex legs and arms, and also to block his breathing when he is immersed. Concerning this fact to phylogenies of human motor skills that explains the human has changed from the water to the ground, from the aquatic species to the terrestrial species. This research approachs  babies's motor development in liquid environment, trying to decrease impacts suffered by them and to recuperate the natural and sequential process of intra uterine motor development, relating to Existencial Transubjective Phenomenology to explain this phenomenon.
Keywords: Phenomenology; Motor Development; Epiglottis Reflex